Modified Organosilica Adsorbents with Bactericidal Properties - T.I. Denisova; D.I. Shvetz (Adsorption Science & Technology)
The method of mathematical planning of experiments has been used to determine the optimal conditions for the formation of a two-component organosilica with various compositions modified by metal ions (Cu II , Zn II ) sorbed from their water–ammonia solutions. Through this method, modified forms of silico-polymethylsiloxanes (SG-PMS) containing 1–30 mg/g Cu II ion [SG-PMS(Cu)] and 3–40 mg/g Zn II ion [SG-PMS(Zn)] were synthesized and their adsorption/structural characteristics established. The sorptive capacity of the organosilica sorbents and their modified forms towards pathogenic microflora ( E. coli, S. aureus, P. aeruginosa ), which depend on the concentration of the modified component, the pH of the medium and the sorptional composition, has been evaluated. It was found that the sorption levels of microorganisms increased in the following sorbent-modified range: 30:70 wt% SG-PMS(Al) < 50:50 wt% SG-PMS(Zn) < 50:50 wt% SG-PMS(Cu) and attained values in the range of 81–98% for metal-containing forms depending on the pH of the medium and the nature of the microorganisms. Copper-containing forms of organosilica exhibited an inhibiting effect towards pathogenic microorganisms even at Cu II ion-containing contents of only 1 mg/g.